PEMBINAAN NILAI PENDIDIKAN PROFETIK PADA ANAK MIGRAN INDONESIA DI SANGGAR BIMBINGAN AMPANG MALAYSIA - Suwantoro Suwantoro; Fathorrozy Fathorrozy; Kutsiyyah Kutsiyyah; Muliatul Maghfiroh; Sri Nurhayati; Mad Sa’i (LP2M Universitas Ibrahimy, 2026)
This community service program aimed to strengthen the spiritual and moral awareness of Indonesian migrant children at Sanggar Bimbingan Ampang, Malaysia, through prophetic value education. The activity responded to the absence of a structured character development program, as previous value-based activities had been conducted informally. The program was implemented in a three-hour participatory session involving 25 children aged 7–12 years. The activities included value-based ice breaking, storytelling of prophetic role models, guided discussions, role play, and reflective dialogue. Evaluation was conducted through participatory observation of children’s responses during the activities. The results indicate active engagement and the emergence of early moral awareness, reflected in the children’s understanding of honesty, empathy, responsibility, and spiritual values. These findings show that participatory prophetic education can serve as an initial approach to fostering moral identity among migrant children within diaspora communities.